Momentum-heat-mass transfer analogy in gas-solid packed bed at elevated temperatures - Pešić, Radojica; Bošković-Vragolović, Nevenka; Arsenijević, Zorana; Tadić, Goran; Kaluđerović Radoičić, Tatjana (Journal of Engineering & Processing Management, 2022)
The experimental values of the friction factor (fp) at ambient and elevated temperatures as well as of the heat transfer coefficient (hp) were used to establish the analogy among momentum and heat transfer in gas-solid packed beds of mono-sized spherical glass particles, as jH=fp/22 or jHε=fp/50. Also, Chilton-Colburn type of momentum-mass transfer analogy was confirmed. These findings are valid for the range of the modified Reynolds number Re’p≈20-130. The experiments related to fp were performed by measuring the pressure drop across the packed bed of particles (0.58, 0.92, 1.04, 1.20, 1.94, 2.98, 3.91 and 4.91 mm diameters) heated to the desired temperature by hot air (temperatures from 20ºC to 350ºC). The range of gas superficial velocity was from 0.05 to 0.99 m/s and the bed porosities were from 0.357 to 0.430. The experiments related to hp were performed by recording the temperatures of the cold aluminium test spheres (6, 12 and 20 mm dimeters) with embedded K-type (Ni/Al) thermocouples, immersed into the hot packed bed of particles (1.20, 1.94 and 2.98 mm diameters at temperatures from 100 to 300ºC) until the thermal equilibrium was reached. The superficial gas velocity and bed porosity varied from 0.30 to 0.79 m/s and from 0.392 to 0.406, respectively. New correlation for prediction of the heat transfer factor has been proposed in the form jHε=0.30(Re’p)-0.30.The analogies defined in this way leave the possibility of determining the value of the heat and mass transfer coefficients on the basis of the value of the friction factor, which is more common in the literature.